2016
DOI: 10.11604/pamj.2016.24.182.6446
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia in children when using clonidine in addition to fentanyl with bupivacaine given caudally

Abstract: The aim of the study was to evaluate the efficacy of clonidine in association with fentanyl as an additive to bupivacaine 0.25% given via single shot caudal epidural in pediatric patients for postoperative pain relief. In the present prospective randomized double blind study, 40 children of ASA-I-II aged 1-5 years scheduled for infraumblical surgical procedures were randomly allocated to two groups to receive either bupivacaine 0.25% (1 ml/kg) with fentanyl 1 μg/kg and clonidine 1μg/kg (group I) or bupivacaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Two studies evaluated the efficacy of caudal epidural anesthesia on postoperative analgesia in children undergoing orchiopexy and inguinal hernia repair. 30 , 40 One study evaluated three different volumes of 0.25% levobupivacaine (low: 0.6 mL/kg; middle: 0.8 mL/kg; and high: 1.0 mL/ kg) and reported that the postoperative analgesic consumption at 6, 12, and 24 hours following surgery did not differ among groups. The postoperative pain was evaluated using the CHIPPS instrument which was not statistically different among groups at any time period.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies evaluated the efficacy of caudal epidural anesthesia on postoperative analgesia in children undergoing orchiopexy and inguinal hernia repair. 30 , 40 One study evaluated three different volumes of 0.25% levobupivacaine (low: 0.6 mL/kg; middle: 0.8 mL/kg; and high: 1.0 mL/ kg) and reported that the postoperative analgesic consumption at 6, 12, and 24 hours following surgery did not differ among groups. The postoperative pain was evaluated using the CHIPPS instrument which was not statistically different among groups at any time period.…”
Section: Resultsmentioning
confidence: 99%
“…23 The main limitations of this observational study were that we focused only on the assessment of the risk factors for PRAEs in children undergoing ambulatory surgery, and we did not investigate the repeatability and reproducibility of COLDS scoring, in addition to the lack of blinding. The second limitation was that we did not study the role of our anesthetic protocol, 24 which did not include regional analgesic techniques, 25 in increasing the risk of PRAEs, as we used the same protocol for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many tools use both physiological and behavioral measures to determine pain scores [ 11 ]. Local anesthesia is a simple-to-use technique for post-operative pain management [ 2 ]. Toxicity of local anesthetics is mostly attributable to high plasma concentrations of such agents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, local anesthesia is commonly used, as it is a reliable, safe, and easy method of pain control. Therefore, it is common to inject local anesthetics at the end of surgery to relive postoperative pain [ 2 ]. Lidocaine is often used as local anesthesia because it is associated with a fast onset of sensory blockade and good efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation